2016
DOI: 10.1074/jbc.m116.738765
|View full text |Cite
|
Sign up to set email alerts
|

Glycosynthase Mutants of Endoglycosidase S2 Show Potent Transglycosylation Activity and Remarkably Relaxed Substrate Specificity for Antibody Glycosylation Remodeling

Abstract: Glycosylation can exert a profound impact on the structures and biological functions of antibodies. Glycosylation remodeling using the endoglycosidase-catalyzed deglycosylation and transglycosylation approach is emerging as a promising platform to produce homogeneous glycoforms of antibodies, but the broad application of this method will require the availability of highly efficient glycosynthase mutants. We describe in this paper a systematic site-directed mutagenesis of an endoglycosidase from Streptococcus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
139
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(159 citation statements)
references
References 49 publications
2
139
0
Order By: Relevance
“…Endo-S and its glycosynthase, which specifically and efficiently acts on the IgG-Fc domain of N-glycans, have been used for chemoenzymatic synthesis of IgGs with structurally defined glycoforms for functional studies (43)(44)(45). More recently, Endo-S2 was shown to have a more flexible substrate specificity and high efficiency in transferring complex, hybrid, and high mannose-type N-glycans onto corefucosylated or non-fucosylated IgG molecules (46).…”
mentioning
confidence: 99%
“…Endo-S and its glycosynthase, which specifically and efficiently acts on the IgG-Fc domain of N-glycans, have been used for chemoenzymatic synthesis of IgGs with structurally defined glycoforms for functional studies (43)(44)(45). More recently, Endo-S2 was shown to have a more flexible substrate specificity and high efficiency in transferring complex, hybrid, and high mannose-type N-glycans onto corefucosylated or non-fucosylated IgG molecules (46).…”
mentioning
confidence: 99%
“…Similar phenomenon with this fucosidase was observed in the glycosylated and deglycosylated Fc domain of IgG antibodies including rituximab (unpublished data). A recent report also showed that the α-fucosidase from Bacteroides fragilis had similar selectivity in defucosylation 3721 . Finally, Endo-A catalyzed transglycosylation of glycoform 9 with the azide-Man3GlcNAc oxazoline gave the novel glycoform 10 .…”
Section: Resultsmentioning
confidence: 90%
“…Utilizing different substrate selectivity of respective endoglycosidases, we and other labs have developed a tool box of endoglycosidases and related glycosynthases for glycoprotein synthesis and glycosylation remodeling 12-15 . These include the glycosynthases derived from Endo-A (from Arthrobacter protophormiae ) 16 , Endo-M (from fungus Mucor hiemalis ) 17,18 , and Endo-D (from bacterium Streptococcus pneumoniae ) 19 of the glycoside hydrolase (GH) family 85 (GH85), as well as those derived from Endo-S (from Streptococcus pyogenes ) 20 , Endo-S2 21 (from Streptococcus pyogenes ), and Endo-F3 (from Elizabethkingia miricola ) 22 of the GH family 18 (GH18). This platform has been especially efficient in synthesis of various glycopeptides and for remodeling of simple glycoproteins such as ribonuclease B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core fucosylation of the Fc domain N-glycans plays a pivotal role in modulating the functions of antibodies and their therapeutic efficacy 8,74 . We have previously developed a chemoenzymatic Fc glycan remodeling method that consists of deglycosylation and glycosynthase-catalyzed glycan transfer to produce homogeneous Fc glycoforms 65,66,75 . If the fucoligase mutant could act on intact antibody, then it would further expand the repertoire of the toolbox for antibody Fc glycan engineering.…”
Section: Resultsmentioning
confidence: 99%